2006
DOI: 10.1515/cclm.2006.094
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocyte count, mean reticulocyte volume, immature reticulocyte fraction, and mean sphered cell volume in elite athletes: reference values and comparison with the general population

Abstract: No statistically significant differences were observed for Retics, MRV, IRF, and MSCV between elite athletes and controls. Significant differences were observed for haemoglobin (Hb), erythrocytes, haematocrit (Ht), and mean corpuscular volume. Moreover, no statistical differences were observed among different sports, whereas differences were remarked in football and rugby players between the samples drawn before the start of competitive season and the samples drawn during the season, demonstrating that reticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
4
25
1
1
Order By: Relevance
“…We are aware of only one study using the ADVIA system for reticulocyte determinations with results separately reported for normal adult male subjects [25]: such results showed lower reticulocyte number and immaturity than in the subjects of the present study (normal values reported: reticulocyte number: 29-69 x10 3 /L; reticulocyte %RBC: 0.5-1.4; MRF: 1.5-10.7%; HRF: 0-2.0%). Other results of reticulocytes determinations were more similar to those found in this study, but they were in relation to samples including children and ill subjects [26,27], or were obtained with instruments other than the ADVIA system [28].…”
Section: Discussionsupporting
confidence: 84%
“…We are aware of only one study using the ADVIA system for reticulocyte determinations with results separately reported for normal adult male subjects [25]: such results showed lower reticulocyte number and immaturity than in the subjects of the present study (normal values reported: reticulocyte number: 29-69 x10 3 /L; reticulocyte %RBC: 0.5-1.4; MRF: 1.5-10.7%; HRF: 0-2.0%). Other results of reticulocytes determinations were more similar to those found in this study, but they were in relation to samples including children and ill subjects [26,27], or were obtained with instruments other than the ADVIA system [28].…”
Section: Discussionsupporting
confidence: 84%
“…Athletes (n = 106) males Controls (n = 73) Coulter LH750; rugby, soccer, alpine ski; before the start of competition season (Banfi et al 2006b) Hb ( Athletes (n = 60) males b Controls (n = 14) b Bayer Advia120; speed skating; during competition season (Mayr et al 2006) Eur J Appl Physiol (2011) 111:9-16 13 Hemocue; rowing; season phase not specified (Johansson et al 2009) all the studies investigating the variations of haematological parameters during the competition season were performed on teams. Therefore, the potential iron dietary deficiency that occurred in some athletes has little influence on mean haematological values, as well as on their variations associated with training and competitions.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in haematological parameters can be induced by training for specific disciplines, acute effects of exercise, seasonal adaptations and by special training regimes such as endurance or strength training (Schumacher et al 2000;Banfi et al 2006;Di Santolo et al 2008;Dopsaj et al 2008). Athletes, both male and female, who predominantly require an aerobic source of energy, had the largest value of haematological parameters that provide information regarding cell volume as well as the amount of haemoglobin that they contain.…”
Section: Discussionmentioning
confidence: 99%